Deep sowing of dry direct-seeded rice: cultivar differences in seedling establishment and grain yield - Kanno, Noriko; Garcia, Ricardo; Suralta, Roel R.; Corales, Aurora M.; Bueno, Crisanta S.; Banayo, Niño P.M.C.; Sta. Cruz, Pompe C.; Kumar, Virender; Kato, Yoichiro (Informa UK Limited, 2023)
Dry direct seeding of rice (DDSR) is being increasingly used in water-scarce areas across Asia. When drought occurs, deep sowing may enable germinating seeds to utilize the residual moisture below the surface. Our objective was to examine the effects of different sowing depths on DDSR crop growth. Two yield experiments, one in the Philippines and the other in Japan, were established in rainfed lowlands, but drought did not occur. Across the experiments, sowing at a depth of 6 to 7 cm reduced the percentage of emergence compared with sowing at a depth of 1 to 2 cm (25% vs. 73%), which resulted in lower yield (3.5 vs. 4.4 t ha−1). The relative yield (deep-sowing/shallow-sowing) was positively correlated with the percentage emergence under deep sowing. Cultivars with no significant yield reduction under deep sowing maintained high emergence (>30%) under deep sowing. Seedling’s ability to emerge after deep sowing greatly differed among cultivars: the percentage emergence ranging from 0% to 18% from a depth of 8 to 10 cm, and from 11% to 44% from a depth of 6 to 7 cm. An ancillary field experiment was conducted under drought during the dry season in the Philippines: deep sowing increased the percentage emergence compared with shallow sowing (41% vs. 5%), when the soil surface was severely dry. Our results suggest that choosing cultivars that can tolerate deep sowing is a prerequisite for using deep sowing in DDSR, and that future breeding of DDSR should focus on this tolerance.